Constructing Synthetic Political Identity: A Semiotic And Framing Study Of Ai-Generated Images In Indonesia’s 2024 Election - Anton Sudibyo; Adi Nugroho (ETTISAL : Journal of Communication, 2026)
Artificial Intelligence (AI) increasingly shapes contemporary political communication, including how candidate identities are constructed and circulated. This study analyzes how AI-generated images in Indonesia’s 2024 Presidential Election, particularly visuals associated with the Prabowo–Gibran campaign functioned as semiotic and discursive instruments in political branding. Using a qualitative approach combining Barthes’ semiotic analysis and Entman’s framing theory, the research examines three prominent AI-generated visuals alongside media coverage and public responses. The findings show that AI-produced aesthetics generate emotional legitimacy through symbolic softening marked by cuteness, warmth, and familial intimacy while reinforcing myths of youthfulness, continuity, and technological modernity. Media and public framings alternated between viewing these visuals as creative political innovation and critiquing them as synthetic manipulation, reflecting ambivalent attitudes toward authenticity in AI-mediated politics. The study concludes that AI operates as a semiotic and discursive actor that co-constructs political identity through aesthetic and affective cues. These insights contribute to discussions on algorithmic aesthetics, synthetic affect, and the evolving dynamics of political branding in digital-era elections.